2009
DOI: 10.1007/s00418-009-0583-3
|View full text |Cite
|
Sign up to set email alerts
|

An active mechanism flanks and modulates the export of the small ribosomal subunits

Abstract: The modalities of export of the ribosomal subunits from the nucleolus to the nuclear pores have been only partially clarified since it is not yet clear whether the movements depend purely on diffusion or also from an active process. Recently, we suggested the existence of an active transport mechanism of a subset (10-12%) of the small ribosomal subunits (SSU) (Cisterna et al. in 2006, Faseb J). Here, we give further evidence that an active, motor protein-mediated process exists for the SSU transport from the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Nuclear actin is also involved in the regulation of mRNA and rRNA transcription and is crucial in the active nuclear-to-cytoplasm transport of both mRNA (reviewed in 34 ) and pre-ribosomal subunits. 35,36 Therefore, the significantly lower amount of nuclear actin observed in the interchromatin space and nucleoli of old animals (Figure 2A) is consistent with the previously shown reduction in transcriptional rate and impairment of RNA export in the aged skeletal muscle. 22,29 As for the nucleolus, a previous study 21 a reduction in rRNA transcription and processing as indicated by decrease of the dense fibrillar component 21 where these processes are known to take place.…”
Section: Resultssupporting
confidence: 90%
“…Nuclear actin is also involved in the regulation of mRNA and rRNA transcription and is crucial in the active nuclear-to-cytoplasm transport of both mRNA (reviewed in 34 ) and pre-ribosomal subunits. 35,36 Therefore, the significantly lower amount of nuclear actin observed in the interchromatin space and nucleoli of old animals (Figure 2A) is consistent with the previously shown reduction in transcriptional rate and impairment of RNA export in the aged skeletal muscle. 22,29 As for the nucleolus, a previous study 21 a reduction in rRNA transcription and processing as indicated by decrease of the dense fibrillar component 21 where these processes are known to take place.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, nascent ribosomal particles seem to be accompanied by NM1 during transport from nucleolus toward nuclear pores [13] and blocking of NM1 or actin by antibodies results in nuclear retention of small ribosomal subunits [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, MVI-S6 interactions have been also shown for skeletal muscle and myogenic cells [Lehka et al, unpublished]. It is noteworthy that an ATP-dependent spatial association of S6-containing small ribosomal subunits (SSUs) with NMIC and actin within the nuclear compartments and at the nuclear pores has been shown in HeLa cells (Cisterna et al, 2006;Cisterna et al, 2009). The authors' suggestion that NMIC is involved in the actin-dependent export of SSUs to the cytoplasm supports our hypothesis that MVI could be engaged in transporting ribosome components to and from the nucleus/nucleolus.…”
Section: Discussionmentioning
confidence: 99%